The Analysis of Good Corporate Governance, Corporate Social Responsibility and, Firm Size Toward Firm Value - Volta Diyanto; Riska Natariasari (Indonesian Journal of Economics, Social, and Humanities, 2019)
This research aims to analyze the effect of good corporate governance, corporate social responsibility, and the firm size towards the firm value. The population was banking firms listed in Indonesia Stock Exchange period 2015-2018. Samples used were 28 firms. The analysis method used multiple linear regression. The research results show that managerial ownership does not have effect towards the firm value. Institutional ownership and firm size have positive effect towards the firm value. Corporate social responsibility has negative effect towards the company value.